Kaolin Foliar Application Has a Stimulatory Effect on Phenylpropanoid and Flavonoid Pathways in Grape Berries - Conde, Artur; Pimentel, Diana; Neves, Andreia; Dinis, Lia-Tânia; Bernardo, Sara; Correia, Carlos M.; Gerós, Hernâni; Moutinho-Pereira, José (Frontiers in Plant Science, 2016)
Drought, elevated air temperature and high evaporative demand are increasingly frequent during summer in grape growing areas like the Mediterranean basin, limiting grapevine productivity and berry quality. The foliar exogenous application of kaolin, a radiation-reflecting inert mineral, has proven effective in mitigating the negative impacts of these abiotic stresses in grapevine and other fruit crops, however, little is known about its influence on the composition of the grape berry and on key molecular mechanisms and metabolic pathways notably important for grape berry quality parameters. Here, we performed a thorough molecular and biochemical analysis to assess how foliar application of kaolin influences major secondary metabolism pathways associated with berry quality-traits, leading to biosynthesis of phenolics and anthocyanins, with a focus on the phenylpropanoid, flavonoid (both flavonol- and anthocyanin-biosynthetic) and stilbenoid pathways. In grape berries from different ripening stages, targeted transcriptional analysis by qPCR revealed that several genes involved in these pathways – VvPAL1, VvC4H1, VvSTSs, VvCHS1, VvFLS1, VvDFR, and VvUFGT - were more expressed in response to the foliar kaolin treatment, particularly in the latter maturation phases. In agreement, enzymatic activities of phenylalanine ammonia lyase (PAL), flavonol synthase (FLS) and UDP-glucose:flavonoid 3-O-glucosyltransferase (UFGT) were about 2-fold higher in mature or fully mature berries from kaolin-treated plants, suggesting regulation also at a transcriptional level. The expression of the glutathione S-transferase VvGST4, and of the tonoplast anthocyanin transporters VvMATE1 and VvABCC1 were also all significantly increased at véraison and in mature berries, thus, when anthocyanins start to accumulate in the vacuole, in agreement with previously observed higher total concentrations of phenolics and anthocyanins in berries from kaolin-treated plants, especially at full maturity stage. Metabolomic analysis by reverse phase LC-QTOF-MS confirmed several kaolin-induced modifications including a significant increase in the quantities of several secondary metabolites including flavonoids and anthocyanins in the latter ripening stages, probably resulting from the general stimulation of the phenylpropanoid and flavonoid pathways.